The effectiveness of using multiple intelligence activities in listening comprehension and improving students' interest - Alilateh, Atikah; Widyantoro, Agus (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2019)
This study aims to find out (1) the effectiveness difference between the use of multiple intelligence activities and the conventional activities in listening comprehension, and in the students’ interest in learning English. This study used the quantitative method. The study design was quasi- experimental with the pre-test and the post-test group design. The experimental class used 5 categories of multiple intelligences namely; linguistic intelligence, logical/mathematical intelligence, visual intelligence, musical intelligence, and naturalist intelligence. This study used a listening comprehension test and a questionnaire as the research instruments for collecting the data. The technique of the data analysis in this study was MANOVA. The result shows that: (1) the use of multiple intelligence in listening comprehension is more effective than the conventional activities with sig 0.000; (2) the use of multiple intelligence activities in students’ interest in learning English is more effective than the conventional activities with sig 0.000.